ESTIMATING SOYBEAN PRODUCTION EFFICIENCY IN IRRIGATED AREA OF BRANTAS RIVER BASIN - Masdjidin Siregar; Sumaryanto Sumaryanto (Indonesian Journal of Agricultural Science, 2003)
Soybean has an important role in Indonesian diet, especially as source of protein, fat, mineral, and vitamin. Given the relatively stagnant technology, efficiency improvement at farm level would probably be an appropriate way to increase soybean production in the near future. The objective of this paper was to estimate the technical efficiency of soybean production in irrigated area of Brantas river basin and analyze factors affecting technical inefficiency level. The results indicated that the technical efficiency of soybean production in the sites was around 83%. The analysis, however, failed to identify the determinants of technical inefficiency because none of the parameters in the analysis was significant. Further study is required to identify the determinants such that the target groups of extension can be specifically determined. Since K2O fertilizer significantly affected soybean production while P2O5 and N fertilizers did not, the first step to improve the technical efficiency of soybean production was to provide soybean farmers with recommendation regarding balanced amount of fertilizers. The recommendation, however, should be derived from local verification trial in each site.